DEFINITION OF THE RECONNECTION RATE OF MOST POWERFUL SOLAR FLARES - Sarsembayeva, A.; Belisarova, F.; Odsuren, M.; Sarsembay, A.; Tutebayeva, A.; Orazymbet, A.; Abyshev, M. (Academic Scientific Journal of Computer Science, 2020)
We observed top 10 X-class solar flares registered in the period November 1997 - September 2017. We measure physical parameters of 10 solar flares, such as the temporal scale, size, and magnetic flux density, and find that the sizes of flares tend to be distributed more broadly as the GOES class becomes weaker and that there is a lower limit of magnetic flux density that depends on the GOES class. We also made a brief analysis of solar flares registered in these days, also has shown the duration of time and peak of solar flares in Universal time. We have identified several physical quantities of solar flares and estimated reconnection rate of solar flares. To determine the physical parameters we used images taken with the AIA instrument on board SDO satellite at wavelengths 131 Å, 174 Å, 193 Å, 211 Å, 335 Å, 1600 Å, 1700 Å, 4500 Å, SXT - pictures, HMI Magnetogram, SOLIS Chromospheric Magnetogram, GOES XRT-data. We estimate reconnection inflow velocity, coronal Alfven velocity, and reconnection rate using the observed values. The inflow velocities are distributed from a few km s-1 to several tens of km s-1, and the Alfven velocities in the corona are in the range from 103 to 104 km s-1. Hence, the reconnection rate is 10-3. We find that the reconnection rate in a flare tends to decrease as the GOES class of the flare increases.